Facile one-step synthesis of quaternary AgInZnS quantum dots and their applications for causing bioeffects and detecting Cu2+. Issue 16 (3rd March 2020) - Han, Xiao-Le; Li, Qingyu; Hao, Hao; Liu, Chenyin; Li, Run; Yu, Fan; Lei, Jiawen; Jiang, Qingqing; Liu, Yi; Hu, Juncheng
Abstract : Water-soluble AgInZnS quantum dots were synthesized with glutathione as a stabilizer by a facile one-step method based on a hydrothermal reaction at 110 °C. It exhibited excellent optical properties, which can be used as sensor to detect Cu 2+ . Abstract : Water-soluble AgInZnS quantum dots (AIZS QDs) were synthesized with glutathione (GSH) as a stabilizer by a facile one-step method based on a hydrothermal reaction between the nitrate salts of the corresponding metals and sodium sulfide as a sulfide precursor at 110 °C. The optimal reaction conditions (temperature, time, pH, and the molar ratios of the precursors) were studied. According to the data from TEM, XPS, and XRD, AIZS QDs were characterized with excellent optical properties. The results showed that the aqueous-dispersible AIZS QDs were quasi-spherical and their average diameter was 3.51 nm. Furthermore, the cytotoxicity of AIZS QDs was investigated by microcalorimetry and microscopy techniques (confocal microscopy and TEM). The data revealed that AIZS QDs exhibited low toxicity, biocompatibility, and good water stability, due to which they could be used as a fluorescent probe for bioimaging and labeling. In addition, AIZS QDs could be used as a sensor to detect Cu 2+ because the fluorescence of AIZS QDs was quenched by Cu 2+ .